Ecological interactions between invasive and native species (Zoological Records and Reviews, 2024)
Biological invasions rank among the leading drivers of global biodiversity loss, yet the mechanistic pathways throughwhich invasive species alter native community structure -- competition, predation, hybridisation, disease transmission,and ecosystem engineering -- remain incompletely quantified in multi-species field contexts. This study characterisesecological interactions between four established invasive species -- Procyon lotor (raccoon), Trachemys scripta elegans(red-eared slider), Pseudorasbora parva (topmouth gudgeon), and Fallopia japonica (Japanese knotweed, as habitatmodifier) -- and their native ecological counterparts across 12 freshwater and riparian sites in the Netherlands andBavaria, Germany (n = 8,614 individual records, 2021-2023). Competitive displacement was quantified by comparingnative species occupancy and abundance at invaded versus uninvaded paired sites. Procyon lotor reduced nativewaterbird nest success by 38.4 +- 6.2% through egg predation (generalised linear mixed model: z = 4.81, p < 0.001).Trachemys scripta elegans competitively displaced Emys orbicularis at 8 of 9 co-occurrence sites, reducing native turtlebasking time by 61.3 +- 8.4%. Pseudorasbora parva presence reduced native cyprinid species richness by 2.8 +- 0.6species per site (t(10) = 4.63, p < 0.001), mediated by both competition for zooplankton resources and rosette virus(Sphaerothecum destruens) transmission. Fallopia japonica invasion reduced riparian ground-dwelling invertebraterichness by 44.2% within invaded patches relative to adjacent uninvaded margins. These findings quantify multi-pathwayinvasion impacts and inform priority ranking for management interventions under the EU Invasive Alien SpeciesRegulation (EU 1143/2014).
Keywords: invasion ecology; riparian ecology; EU IAS Regulation; native species; competitive displacement; Fallopia japonica; Pseudorasbora parva; Trachemys scripta elegans; Procyon lotor; biological invasion